Mosby's medical, nursing, & allied health dictionary - Anderson, Douglas M.; Keith, Jeff; Novak, Patricia D.; Elliot, Michelle A. (Mosby, 2002)
This dictionary of medical nursing and allied health includes: an alphabetical organization with no subentries; comprehensive definitions for key entries such as major diseases, disorders and procedures; detailed drug entries; and the Colour Atlas of Human Anatomy